Penentuan Nilai SPF Losion Minyak Bunga Matahari - Zenny Zenny (Herbal Medicine Journal, 2021)
The skin is the most extensive human body organ that protects the skin from ultraviolet (UV) radiation. Excessive exposure to sunlight can cause other diseases that are harmful to human health, such as inflammation of the skin or burning skin. The natural defense system of human skin cannot protect the skin perfectly so it takes a sunscreen to help prevent damage to various skin conditions. Sunflower oil is a vegetable oil that is rich in vitamin E which acts as an antioxidant. The purpose of this study was to determine the effect of adding various variations of sunflower oil concentration to the SPF value of sunscreen lotion. The sunscreen lotion is made in 5 formulas namely Formula 1 (base lotion), Formula 2 (base of positive control), Formula 3 (1% sunflower oil), Formula 4 (5% sunflower oil) and Formula 5 (sunflower oil) 10%). Formula 2 to Formula 5 is added with octyl methoxycinamate (7.5%) and titanium dioxide (2.5%). Determination of SPF value was carried out by spectrophotometry Uv-Vis at wavelengths of 290-320 nm. The SPF results indicate that the higher the concentration of sunflower oil, the higher the SPF value produced. Formula 1 SPF values ​​are 11.71, Formula 2 is 20.73, Formula 3 is 22.98, Formula 4 is 24.66 and Formula 5 is 28.18. From the results of this study, it was concluded that the addition of various concentrations of sunflower oil can increase the SPF value.